Case Report: Repeated esophageal obstruction in a patient with type 3C diabetes mellitus - Koyama, Katsumasa; Anno, Takatoshi; Takenouchi, Haruka; Kimura, Tomohiko; Kaku, Kohei; Kaneto, Hideaki (Frontiers in Endocrinology, 2023)
Although diabetic neuropathy is a well-known cause of gastrointestinal motility disorders, it is rare that diabetic neuropathy brings about esophageal obstruction. Here, we report a case with Type 3C diabetes mellitus (DM) lasting over 15 years and repeated esophageal obstruction resulting in chicken-meat-induced esophageal obstruction and candidiasis. This case highlights the importance of management of DM to prevent the development of complications such as diabetic neuropathy and associated symptoms.